Meningioma of the Pineal Region — Differential Radiologic Aspects of Pineal Region Tumors Based on a Clinical Case - Avelar, Tiago Marques; Paiva, Aline Lariessy Campos; Costa, Márcio Alexandre Teixeira da; Aguiar, Guilherme Brasileiro de; Vitorino, João Luiz; Veiga, José Carlos Esteves (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Pineal region tumors are uncommon among neoplasm of the central nervous system, with this region being the most heterogeneous in terms of histological types. Meningiomas are rarer still, but can be found at this site, with origins in either the velum interpositum or falcotentorial junction. Neuroimaging exams can distinguish malignant from benign lesions besides helping to define the origin of the lesion as the pineal parenchymal or surrounding structures. We report the case of a woman with a pineal region tumor in which differential diagnoses included meningioma and germinoma, with confirmation of the former based on radiological characteristics and histopathology. In addition, a brief review of differential diagnoses and approaches for cases of lesions in this region is provided.
Keywords: meningioma; pineal gland; brain neoplasms